Protective antibodies inhibit reovirus internalization and uncoating by intracellular proteases. - Virgin, H W (1994)
We identified in vitro correlates of in vivo protection mediated by nonneutralizing antibodies specific for reovirus capsid proteins. We defined mechanisms of antibody action by analyzing monoclonal antibody (MAb) effects at sequential steps in reovirus serotype 3 strain Dearing (T3D) infection of L cells. Two types of experiments showed that protective MAbs specific for the outer capsid proteins sigma 3 or mu 1 inhibited T3D infection independent of effects on binding. First, MAbs which had no effect on T3D binding inhibited T3D growth. Second, MAb-coated T3D attached to L cells did not replicate as efficiently as T3D without bound antibody. We therefore defined sigma 3-specific MAb effects on postbinding steps in T3D infection. T3D coated with MAb sigma 3-10G10 exhibited prolonged sensitivity to growth inhibition by ammonium chloride. Since ammonium chloride inhibits endosomal acidification and proteolytic processing of the T3D capsid, this suggested that MAbs inhibit early steps in T3D infection. This was confirmed by direct demonstration that several sigma 3-specific MAbs inhibited proteolytic uncoating of virions by fibroblasts. We identified two mechanisms for antibody-mediated inhibition of virion uncoating: (i) inhibition of internalization of T3D-MAb complexes bound to the cell surface, and (ii) inhibition of intracellular proteolysis of the T3D capsid. Studies using a cell-free system confirmed that sigma 3-specific MAbs directly block proteolytic uncoating of the T3D virion. In addition, we found that sigma 3-specific MAbs block (and therefore define) two distinct steps in proteolytic uncoating of the reovirion. We conclude that antibodies which are protective in vivo inhibit postbinding events in reovirus infection of permissive cells. Protective antibodies act by inhibiting internalization and intracellular proteolytic uncoating of the virion. Analysis of postbinding mechanisms of MAb action may identify targets for vaccine development and antiviral therapy.